LIMITATIONS OF HUMAN LEUKOCYTE ANTIGEN MOLECULAR TYPING METHODS FOR PATIENTS WITH ACUTE MYELOID LEUKEMIA RELAPSE AFTER HEMATOPOIETIC STEM CELL TRANSPLANTATION - L.O. Sishchuk; I.I. Tubaltseva; N.A. Tsokolenko; A.O. Maksymchuk; A. V. Kukhol; V.V. Andrusenko; A.O. Mazanova; Y.A. Hrohul (Biotechnologia Acta, 2025)
Aim. The work purposed to compare molecular typing methods with different resolutions in clinical cases without loss of heterozygosity (LOH) in HLA genes.